ONLINE THESIS GUIDANCE MANAGEMENT INFORMATION SYSTEM AT MITRA INDONESIA UNIVERSITY - Fatimah Fahurian; Khozainuz Zuhri (Jurnal TAM (Technology Acceptance Model), 2020)
The process of guiding the final project at the University of Mitra Indonesia has several obstacles when the process of working on student skirpsi is hampered, the difficulty of students and supervisors to conduct the guidance process. To overcome the existing problems, one effort is to build a thesis guidance information system. Therefore, the author proposes a thesis guidance information system that can be accessed anywhere and anytime. The online thesis guidance system that has been built can be applied to facilitate lecturers in examining and revising documents sent by students so that the design of an online thesis guidance system can help the final project guidance process at theUniversity of Mitra Indonesia, starting from the student registration process, sending files and interacting with the guidance process between lecturers and students. In addition, with the existence of an online thesis guidance system, it is expected that the process of implementing thesis guidance for students and lecturers will become clearer and more targeted.